2009
DOI: 10.1002/gps.2314
|View full text |Cite
|
Sign up to set email alerts
|

Working memory in early Alzheimer's disease: a neuropsychological review

Abstract: Background: Reports of the extent of working memory (WM) impairment in early Alzheimer's disease (AD) have been inconsistent. Using the model of WM proposed by Baddeley, neuropsychological evidence for the impairment of WM in early AD is evaluated. Method: Literature searches were performed using Medline, PsycINFO and Embase databases. Individual papers were then examined for additional references not revealed by computerised searches. Results: Phonological loop function is intact at the preclinical and early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
112
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(120 citation statements)
references
References 109 publications
(177 reference statements)
7
112
0
1
Order By: Relevance
“…These differences at T1 should most likely testify fairly different trajectories in the disease progression (see also Clearly, behind the overall cognitive decline measured by a very popular but rather crude index like the MMSE, a more complex pattern is hidden. In particular, the tests where most of the BAD-responders showed a time-related decline were those tackling executive functions [47], a finding consistent with what is described as the typical progression of the disease [48][49][50][51][52]. Thus, although the use of the MMSE test to monitor the disease progression has the natural charm of the simplicity involved in both test administration and test scoring, it is clear that one could achieve a more detailed description of the neuropsychological trajectories associated with the disease by using a more extensive neuropsychological test battery.…”
Section: Discussionsupporting
confidence: 71%
“…These differences at T1 should most likely testify fairly different trajectories in the disease progression (see also Clearly, behind the overall cognitive decline measured by a very popular but rather crude index like the MMSE, a more complex pattern is hidden. In particular, the tests where most of the BAD-responders showed a time-related decline were those tackling executive functions [47], a finding consistent with what is described as the typical progression of the disease [48][49][50][51][52]. Thus, although the use of the MMSE test to monitor the disease progression has the natural charm of the simplicity involved in both test administration and test scoring, it is clear that one could achieve a more detailed description of the neuropsychological trajectories associated with the disease by using a more extensive neuropsychological test battery.…”
Section: Discussionsupporting
confidence: 71%
“…Although early and significant episodic memory impairment constitutes the clinical core diagnostic criterion of AD (Dubois et al, 2014), there is increasing evidence of early deficits in WM and executive function in patients with MCI and AD (Crawford et al, 2013;Gagnon and Belleville, 2011;Huntley and Howard, 2010;Kessels et al, 2011;Koppel et al, 2014). Moreover, fMRI studies have also suggested a possible subclinical impairment of WM capacity in healthy APOE Δ4 carriers (Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although deficits in episodic memory characterize AD, there is increasing evidence that working memory (WM), which involves the short-term online storage and manipulation of information, is also impaired during the earliest stages of disease (Huntley and Howard, 2010). Deficits in WM have also been demonstrated using specialized testing in APOE Δ4 carriers (Rosen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in PFC circuitry have long been associated with psychiatric disorders such as schizophrenia and neurodegenerative diseases such as Alzheimer's disease (Cole et al 2011;Fernando and Robbins 2011;Goldman-Rakic and Selemon 1997;Huntley and Howard 2010;Insel and Fernald 2004;Sigurdsson et al 2010). In recent years, the mouse has become a major model organism for the study of such disorders in particular and of cognition and behavior in general, and these mouse models provide powerful genetic tools that allow us to dissect the underlying molecular, cellular, and circuit mechanisms.…”
mentioning
confidence: 99%